Importance of Growth Stages of Rice - Devi, Ayekpam Dollina; Singh, Teekam; Kumari, Megha (Chronicle of Bioresource Management, 2023)
Growth of a crop goes through several process and stages until it is fully developed and reached maturity. Similarly, rice growth progresses through distinct stages: germination, seedling, tillering, panicle initiation, booting, heading, flowering, and maturity. Each stage plays a vital role in determining yield potential and is influenced by environmental conditions, water availability, nutrient management, and pest control. During germination and seedling stages, proper moisture and temperature conditions ensure uniform emergence. The tillering stage enhances canopy development and determines the number of productive shoots. As the plant transitions to the reproductive phase, panicle initiation and booting mark the beginning of grain formation. Heading and flowering are critical for pollination and fertilization, directly affecting grain setting and yield. The maturity stage signifies physiological completion, where grains harden and reach harvest readiness. Effective management of irrigation, fertilization, and pest control throughout these stages ensures optimal growth, minimizes stress, and maximizes productivity. Understanding the growth stages of rice is crucial for improving crop management strategies and ensuring sustainable rice production.